2007
DOI: 10.1529/biophysj.107.108183
|View full text |Cite
|
Sign up to set email alerts
|

Hoogsteen-Paired Homopurine [RP-PS]-DNA and Homopyrimidine RNA Strands Form a Thermally Stable Parallel Duplex

Abstract: Homopurine deoxyribonucleoside phosphorothioates possessing all internucleotide linkages of R(P) configuration form a duplex with an RNA or 2'-OMe-RNA strand with Hoogsteen complementarity. The duplexes formed with RNA templates are thermally stable at pH 5.3, while those formed with a 2'-OMe-RNA are stable at neutrality. Melting temperature and fluorescence quenching experiments indicate that the strands are parallel. Remarkably, these duplexes are thermally more stable than parallel Hoogsteen duplexes and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Unlike in DNA ( 59 ) where experimental evidence has been provided for the isolated existence of such a ps duplex, more detailed data indicating formation of an isolated ps Hoogsteen-paired RNA duplex appear to be lacking to our knowledge. On the other hand, formation of a ps Hoogsteen-paired duplex between a homo-pyrimidine RNA strand and a homo-purine all- R p-phosphorothioate DNA strand has recently been demonstrated ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in DNA ( 59 ) where experimental evidence has been provided for the isolated existence of such a ps duplex, more detailed data indicating formation of an isolated ps Hoogsteen-paired RNA duplex appear to be lacking to our knowledge. On the other hand, formation of a ps Hoogsteen-paired duplex between a homo-pyrimidine RNA strand and a homo-purine all- R p-phosphorothioate DNA strand has recently been demonstrated ( 61 ).…”
Section: Resultsmentioning
confidence: 99%
“…For unmodified oligonucleotides, the thermal stability of parallel duplexes is significantly lower compared to antiparallel WatsonÀCrick duplexes. However, Guga et al found that homopurine PS-Oligos possessing all internucleotide linkages of (R P )-configuration form parallel duplexes with an RNA or 2'-MeO-RNA strand with Hoogsteen complementarity [162]. The parallel orientation of strands was confirmed by fluorescence quenching experiments.…”
Section: For Example the Duplex [All-(s P )-Ps]-da 12 /T 12 Is More mentioning
confidence: 97%
“…Furthermore, Guga's group reported that homopurine DNA phosphorothioates possessing all internucleotide linkages of the R P configuration form stable parallel duplexes. Remarkably, the structures formed with 2′‐ O ‐methyl‐RNA are thermally more stable than unmodified duplexes with antiparallel orientation and the modified forms were also stable under neutral conditions .…”
Section: Parallel Dna and Rna Duplexesmentioning
confidence: 99%
“…Because DNA and RNA with parallel strands could be promising tools in molecular genetics, researchers have shown an interest in improving their physicochemical properties . As a result, various chemical modifications of oligonucleotides have been developed.…”
Section: Parallel Dna and Rna Duplexesmentioning
confidence: 99%